Mechanisms of Anthracycline-Induced Cardiotoxicity: Is Mitochondrial Dysfunction the Answer? - Murabito, Alessandra; Hirsch, Emilio; Ghigo, Alessandra (Frontiers in Cardiovascular Medicine, 2020)
Cardiac side effects are a major drawback of anti-cancer therapies, often requiring the use of low and less effective doses or even discontinuation of the drug. Among the most cardiotoxic agents are anthracyclines that, though being the oldest chemotherapeutic drugs, are still a mainstay in the treatment of solid and hematological tumors. The recent expansion of the field of Cardio-Oncology, a branch of cardiology dealing prevention or treatment of heart complications due to cancer treatment, has greatly improved our understanding of the molecular mechanisms underlying anthracycline-induced cardiotoxicity (AIC). Despite excessive production of reactive oxygen species was originally believed to be the main cause of AIC, recent evidence points to the involvement of a plethora of different mechanisms that, interestingly, mainly converge on deregulation of mitochondrial function. In this review, we will describe how anthracyclines affect cardiac mitochondria and how these organelles contribute to AIC. Furthermore, we will discuss how drugs specifically targeting mitochondrial dysfunction and/or mitochondria-targeted drugs could be therapeutically exploited to treat AIC.